2008
DOI: 10.30843/nzpp.2008.61.6801
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the agdisp ground boom spray drift model

Abstract: AGDISP is a wellestablished spray drift model that has been validated for aerial spraying of forests Recently a prototypical ground boom option has been added to AGDISP This was evaluated in the current study by collecting data from spray trials over a grass sward using a ground boom sprayer and representative application parameters Spray solutions were made up of water sticker adjuvant and a metal cation which was changed for each spray application Deposition from spray drift was measured by analyses of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The ratio of model to measured decreased from an average of 12.4 (by reanalysis of these data) to 7.8 (to 63%) for the New Zealand data (analysis of the results presented in Woodward et al (2008)), while for the Canadian data the average ratio reduced from 3.9 to 1.5 (to 38%) and the Belgian data from 2.9 to 2.2 (to 76%).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…The ratio of model to measured decreased from an average of 12.4 (by reanalysis of these data) to 7.8 (to 63%) for the New Zealand data (analysis of the results presented in Woodward et al (2008)), while for the Canadian data the average ratio reduced from 3.9 to 1.5 (to 38%) and the Belgian data from 2.9 to 2.2 (to 76%).…”
Section: Discussionmentioning
confidence: 85%
“…The New Zealand trials (Woodward et al 2008) reported four treatments using XR11003 and 04 flat fan nozzles at 150 kpa and 300 kpa at a target application rate of 200 litres/ha at 0.5 m above the ground of 0.1 m high grass with a ground speed of 2 m/s. One replicate of four 5 m wide, 20 m long swaths was carried out per treatment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unique to AgDRIFT® is the inclusion of aircraft wake influences on drift (Bilanin et al, 1989). AgDRIFT® contains a tier 1 (a developed regression model) model for ground applications; however Woodward et al (2008) found through in-field testing that AgDRIFT® overpredicted out-of-swath deposition by a factor from 3.5-100. Developments to revise the tier 1 prediction model with a more analytical approach to provide greater accuracy are ongoing (Teske et al 2001, Teske et al, 2004.…”
Section: Mechanistic Analytical Modelsmentioning
confidence: 99%